STRESS STATUS (MILD, MODERATE AND SEVERE) VIZˋ-A-VIZˋ LEADING RISK FACTORS AMONG CLIENT-OWNED DOMESTICATED CATS (Felissilvestriscatus) AFFECTED WITH THE ‘PANDORA’ SYNDROME: A RETROSPECTIVE STUDY - A. Naureen; M. S. Khan; M. A. Khan; A. Maqbool; J. A. Khan; M. Avais1 (Journal of Animal and Plant Sciences, 2017)
The present study was conducted to analyze association b/w depression status (mild, moderate and severe) and different risk factors (n=14) leading to the ‘Pandora’ syndrome among cats. To this end, risk factors were divided into 2 groups on the basis of demography(n=5) and general history (n=9). No particular breed predilection was found, however, majority (n=300) of cats attended were Siamese. Male to female ratio was found to be 2.5:1. Depression status was found to be highly associated (P-value = 0.000) with winter season, and all but one (stranguria; P-value = 0.774) clinical signs.Remaining risk factors were not inclose association with that of depression. This study debunked previous notions like strong association of commercial diets and canned foods with this syndrome, in Pakistan majority fed with home-cooked food. Moreover, cases in Siamese breed were larger than Persian breed. The proportional morbidity rate (PMR) observed was estimated to be 8.7%. The PMR values show more about interests of clinicians rather than the incidence of disease in that population.
Keywords: Depression status; risk factors; ‘Pandora' syndrome; client-owned domesticated cats